Traffic Obedience Since Early Childhood - Hilda Eka Anggraeni; Edi Waluyo (Universitas Pendidikan Ganesha, 2026)
The high number of traffic accidents involving young children indicates the low level of traffic safety awareness from an early age. Traffic safety awareness is an important aspect of character development, particularly in fostering children’s discipline and responsibility. This study aims to analyze the level understanding and obedience of young children toward traffic rules and examine the roles of teachers, parents, the environment, and educational media in shaping children’s traffic discipline behavior. This study employed a quantitative approach using a cross-sectional survey design. The sample consisted of 50 children aged 4–6 years selected through purposive sampling. Data were collected through questionnaires and observations using instruments that had been tested for validity and reliability. Data analysis techniques included Pearson correlation, multiple linear regression, and ANOVA. The findings showed that the teacher’s role was the most significant factor influencing children’s traffic obedience. Educational media such as songs and stories also contributed positively to children’s understanding, while the roles of parents and the environment were not significant in the multiple regression analysis. The regression model demonstrated high accuracy in explaining variations in children’s traffic obedience. This study emphasizes the importance of collaboration between schools, families, and the government in integrating traffic safety education into early childhood learning through interactive and contextual approaches to strengthen children’s discipline and safety awareness from an early age. The implications of this study indicate that traffic safety education should be implemented systematically through role-model-based learning and educational media to develop culture of traffic discipline from early childhood.